Analysis of Difficulties in Understanding Mathematical Concepts In Class VIII Students of SMP Negeri 2 Hiliduho in the 2022/2023 Academic Year - Ika Kartika Hia; Amin Otoni Harefa (Universitas Muhammadiyah Enrekang, 2023)
This research is based on the results of a preliminary study conducted by researchers during the implementation of the Internship at SMP Negeri 2 Hiliduho, a problem was found, namely the understanding of mathematical concepts of students in the poor category. The purpose of this study was to determine the difficulty of understanding mathematical concepts in class VIII students of SMP Negeri 2 Hiliduho and to find out the factors that cause difficulties in understanding mathematical concepts. The instruments used are concept understanding tests, interviews and documentation. Data analysis techniques used are data reduction, data presentation and drawing conclusions. This research was conducted at SMP Negeri 2 Hiliduho in the 2022/2023 Learning Year, totaling 57 people with qualitative descriptive research methods. The results of the study obtained difficulties in understanding the concepts experienced by students, namely: the inability to provide an interpretation of the concepts that have been written down, the inability to remember what a circle must have, the inability to reexpress concepts in other forms, difficulty in developing necessary or sufficient conditions of a concept. Factors causing difficulties in understanding concepts are the lack of use of teaching aids during the learning process, lack of mastery of previous material, and not practicing working on problems.